Production efficiency and agronomic attributes of corn in an integrated crop-livestock-forestry system - Moreira, Elwira Daphinn Silva; Gontijo Neto, Miguel Marques; Lana, Ângela Maria Quintão; Borghi, Emerson; Santos, Claudinei Alves dos; Alvarenga, Ramon Costa; Viana, Maria Celuta Machado (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the agronomic attributes and production efficiency of corn silage and grains in an integrated crop-livestock-forestry (ICLF) system, with intercropping of eucalyptus, corn, and Urochloa cultivars during three crop years. The experimental design was completely randomized, in 2x5x3 split-split plots with four replicates. The plots consisted of corn cropped between eucalyptus rows (ICLF) and in full sun; the subplots, of the forage grasses U. brizantha 'Marandu', U. brizantha 'Xaraés', U. brizantha 'Piatã', U. ruziziensis, and U. decumbens 'Basilisk'; and the split-split plots, of the 2011/2012, 2012/2013, and 2013/2014 crop years. There was no effect of eucalyptus on the silage and grain yields of corn when intercropped with forages in 2011/2012. The production efficiency of silage and grains decreased by 25 and 48%, respectively, in 2012/2013 (12-month-old eucalyptus). There was also a 56% reduction in grain yield in 2013/2014 (24-month-old eucalyptus), compared with full sun. In the year the ICLF system is established, the production efficiency of corn silage and grains is not affected by eucalyptus, but decreases with the development of the trees in the subsequent crop years.